A Metafunction Analysis of Conjunction System in the Opinion Forum of the Jakarta Post Daily Newspaper - Wijayanto, Pikir Wisnu (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
The study aims at finding the meaning of the texts or sentences in detail from the discourse semanticsâ€™ perspectives through metafunctions analysis of conjunction systems introduced by Martin and Rose (2003: 110). This study used qualitative and descriptive methods. The data used in this study is taken from the top three most shared articles by the readers in the "Opinion Forum" of the Jakarta Post in January 2019. They are entitled â€œFree Baâ€™asyir? Why now?â€ by the Editorial Board of Jakarta Post, â€œOur double standards on Jerusalem and Baâ€™asyirâ€ by Kornelius Purba, and â€œQuestioning early release of Ba'asyirâ€ by Carrisa Tehputri. The researcher assesses the extent of utilization of conjunctions in the text by using the four kinds of logic for the conjunction types; addition, comparison, time, and consequence. Based on the analysis of conjunction systems, the article uses four logics of conjunctions both external and internal conjunctions as a logical connection between phrases, clauses, or idioms. First, the three articles used conjunctions to add the meaning of information and become a set of means for adjusting expectations are continuatives. Second, the conjunctions logic used as a comparison that expressed the meaning of similarity and contrast in order to compare or contrast arguments when countering an expectation that the authors have created for the reader. Third, the articles used the conjunctions to express the successive meaning and simultaneous meaning in order to add the information when sequencing events and looking at interconnections between processes. In short, those conjunctions are used to relate activities in sequences and to organize arguments. The last logic conjunctions used in those articles are the consequence with cause, purpose, and condition meaning in order to add the information when giving cause and effect.